Use of Circular RNAs in Diagnosis, Prognosis and Therapeutics of Renal Cell Carcinoma - Osca-Verdegal, Rebeca; Beltrán-García, Jesús; Górriz, José Luis; Martínez Jabaloyas, José María; Pallardó, Federico V.; García-Giménez, José Luis (Frontiers in Cell and Developmental Biology, 2022)
Renal cell carcinoma is the most common type of kidney cancer, representing 90% of kidney cancer diagnoses, and the deadliest urological cancer. While the incidence and mortality rates by renal cell carcinoma are higher in men compared to women, in both sexes the clinical characteristics are the same, and usually unspecific, thereby hindering and delaying the diagnostic process and increasing the metastatic potential. Regarding treatment, surgical resection remains the main therapeutic strategy. However, even after radical nephrectomy, metastasis may still occur in some patients, with most metastatic renal cell carcinomas being resistant to chemotherapy and radiotherapy. Therefore, the identification of new biomarkers to help clinicians in the early detection, and treatment of renal cell carcinoma is essential. In this review, we describe circRNAs related to renal cell carcinoma processes reported to date and propose the use of some therapeutic strategies for renal cell carcinoma treatment.